The effect of EM4 fermented tofu liquid waste addition in the media toward abundance and biomass of Spirulina sp - Debora Utami; Budijono Budijono; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractThe tofu industrial waste is rich in organic materials and it may be used as nutrient sources in the Spirulinasp culture. A study aims to understand the effect of EM4 fermented tofu liquid waste addition in the media toward abundance and biomass of Spirulinasp has been conducted in February to March 2019. The fermented waste was made by mixing 35 L of tofu waste and 35 mL of EM4 and then the mixture was kept for 14 days. There was a CRD method applied, with 4 treatments and 3 replications. The treatments applied was as follows: (T1). 750 ml LCT of fermented waste + 2250 ml of Borehole Water, (T2) 750 ml LCT of fermented waste + 2250 mL of Spring Water (Ground Water), (T3) 750 ml LCT of fermented waste + 2250 mL of RimboPanjang Peat Water, (T4) 750 ml LCT of fermented waste + 2250 mL of Black Water Peat Water of 1000 ml Spirulina culture was added and it was cultured for 14 days. By the end of the experiment, the abundance and biomass of Spirulina was calculated. Result shown that the addition of fermented tofu waste positively affect the growth of Spirulina sp. The best result was obtained in T3 (2,386,000) cells/ml and 0.28 gr biomass in the 7thday.Keywords:fermented waste, microalgae culture, microalgae growth,organic waste